Synthesis and Characterization of 1-(2-(Dimethylamino)ethyl)-6,6a,7,11-tetrahydro-3H,9H-oxazolo[3,4-b]pyrrolo[2,3-h]isoquinolin-9-one: A Zolmitriptan Related Impurity - Mohanty*, eep; Prashanth Reddy, G.; Ch, Arun; Karmakar, ra (Asian Journal of Chemistry, 2013)
We report two different synthetic approaches for the synthesis of 1-(2-(dimethylamino)ethyl)-6,6a,7,11-tetrahydro-3H,9H-oxazolo[3,4-b]-pyrrolo[2,3-h]isoquinolin-9-one (1), an important reference standard for the chemical characterization of zolmitriptan. The starting material isoquinolin-3-one (12) was obtained with good overall yield starting from commercially available L-phenyl alanine (7).